AKTIVITAS EKSTRAK ETANOL KULIT BUAH JENGKOL (Pithecellobium jiringa (Jack) Prain.) SEBAGAI BIOHERBISIDA GULMA BAYAM DURI (Amaranthus spinosus L.) DAN RUMPUT PAITAN (Paspalum conjugatum Berg.) - Hasanah, Siti Nur; Wardoyo, Elvi Rusmiyanto Pancaning; Mukarlina, Mukarlina (Jurnal Protobiont, 2019)
Weed is a plant that grow in undesirable places, especially in the location of cultivated plants. Alelochemical use as bioherbicide is one of the ways in weed control and is safe for the environment. The study was conducted to test the potential of P. jiringa fruit peel extract as bioherbicide on the germination and growth ofA .spinosus and P.conjugatum weeds. The study used a completely randomized design (RAL) with the concentration of extract (P) used consisting of 6 treatments, namely P1 = 0 (control), P2 = 0.1; P3 = 0.2; P4 = 0.3; P5 = 0.4; and P6 = 0.5 g / ml. each treatment was repeated 5 times. The results of the study showed that the concentration extract of 0.5 g / ml was an inverse concentration to inhibit the weed seeds germination ofA.spinosus and P. conjugatum. Good concentration extract to inhibit growth A. spinosus and P. conjugatum is 0.3 g / ml which results in inhibition of plant height, root length, wet weight and dry weight. Based on research conducted on fruit peel extract P. jiringa has the potential as a bioherbicide.